2019
DOI: 10.1097/meg.0000000000001533
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and indicators of use of complementary and alternative medicine in Austrian patients with inflammatory bowel disease

Abstract: Objective Complementary and alternative medicine (CAM) seems to be frequently used among patients with inflammatory bowel disease (IBD). We aimed to determine the prevalence and indicators of CAM use in Austrian IBD patients. Methods In a multicentre cross-sectional study, adult patients with IBD attending 18 Austrian outpatient clinics completed a multi-item questionnaire that recorded use of CAM as well as medical and socioeconomic characteristics. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…However, our study has shown that IBD patients of male gender and lower levels of education were associated with the use of black seeds and honey, respectively. Patients treated with corticosteroids and anti-TNF agents also reported frequent use of CAM, and the most frequently used CAM therapies by this cohort were prayer, meditation, herbal remedies, homeopathy, and mind-body techniques [18]. We did not find that treatment with corticosteroids or anti-TNF-alpha were associated with CAM; however, our results suggest a significant association between treatment with azathioprine and the use of Zamzam water.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…However, our study has shown that IBD patients of male gender and lower levels of education were associated with the use of black seeds and honey, respectively. Patients treated with corticosteroids and anti-TNF agents also reported frequent use of CAM, and the most frequently used CAM therapies by this cohort were prayer, meditation, herbal remedies, homeopathy, and mind-body techniques [18]. We did not find that treatment with corticosteroids or anti-TNF-alpha were associated with CAM; however, our results suggest a significant association between treatment with azathioprine and the use of Zamzam water.…”
Section: Discussioncontrasting
confidence: 75%
“…Previous studies have reported a wide range of CAM agents used for IBD [16,17]. A recent study that surveyed 1,286 Austrian patients with IBD reported that 50.7% used CAM at some point during the disease course [18]. A recent systematic review, published in 2017 by Alrowais et al, estimated a prevalence rate of CAM usage of 90% in Saudi Arabian patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic approaches aim to control the symptoms, increase the quality of life and prevent disease progression and complications [ 2 ]. Studies report that a large proportion of IBD patients show interest in complementary and alternative medicine (CAM) as a therapeutic approach, with herbal medicinal products being among the most commonly used options [ 6 , 7 ]. Scarce evidence on CAM in IBD treatment currently limits the acceptance amongst health care providers and complicates its integration into clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is a sub‐analysis of that project. Materials and methods have been described in detail previously in a manuscript on the use of CAM 8,9 . Briefly, consecutive adult patients over 18 years of age with an established diagnosis of IBD (based on clinical, endoscopic, histological and radiological criteria according to European Crohn's and Colitis Organization guide‐lines) 10,11 attending specialized IBD outpatient clinics were included.…”
Section: Methodsmentioning
confidence: 99%